2020
DOI: 10.1186/s40104-020-00482-x
|View full text |Cite|
|
Sign up to set email alerts
|

Diet induced the change of mtDNA copy number and metabolism in Angus cattle

Abstract: Background: Grass-fed and grain-fed Angus cattle differ in the diet regimes. However, the intricate mechanisms of different beef quality and other phenotypes induced by diet differences are still unclear. Diet affects mitochondrial function and dynamic behavior in response to changes in energy demand and supply. In this study, we examined the mtDNA copy number, mitochondria-related genes expression, and metabolic biomarkers in grass-fed and grainfed Angus cattle. Results: We found that the grass-fed group had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Several pollutants (eg, benzene, 81 particulate matter, 82 and polycyclic aromatic hydrocarbons 83 ) have been associated with changes in mtDNAcn. In addition, dietary factors, 84,85 especially salt intake, 86 might modify the mtDNAcn in blood. This is particularly interesting in the context of CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several pollutants (eg, benzene, 81 particulate matter, 82 and polycyclic aromatic hydrocarbons 83 ) have been associated with changes in mtDNAcn. In addition, dietary factors, 84,85 especially salt intake, 86 might modify the mtDNAcn in blood. This is particularly interesting in the context of CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EGCG-fed mice displayed higher body temperature and mtDNA content in BAT [244]. Of note, not only dietary antioxidants but other nutrients [245] or dietary regimen [246,247], as well as alteration of body composition [65], has shown association with mtDNA copy number, corroborating the hypothesis that diet and health status are strictly linked with the mtDNA function. Conversely, it has been recently demonstrated that alteration of mitochondrial DNA content can modulate antioxidant enzyme expressions and, consequentially, oxidative stress in the cell [248].…”
Section: Antioxidants and Mitochondria: From The General Function To mentioning
confidence: 52%
“…Similarly, lipid content may differ greatly between L. salmonis and C. elongatus larvae based on potential differences in energetics of the two species. Furthermore, relative mtDNA abundance has been linked to mitochondria abundance and metabolic traits in humans and livestock and the differences we detected in the mtDNA copy amounts between C. elongatus and L. salmonis may indicate a difference between the resting metabolism or metabolic potential of the two louse species (Bai et al., 2020; Ganel et al., 2021; Gibbons et al., 2014). As a specialist to salmonids, L. salmonis are relatively rarely occurring and mostly inhabit surface waters, whereas C. elongatus is widely considered a generalist and has been recorded parasitizing over 80 teleosts and elasmobranchs within the North Atlantic, including both pelagic and demersal species (Kabata, 1979; Øines & Heuch, 2007).…”
Section: Discussionmentioning
confidence: 93%